BET 2: Should real resuscitationists use airway checklists?. Issue 6 (19th May 2016) - Hardy, Gareth; Horner, Daniel
Abstract : A short cut review was carried out to establish whether the use of preprocedural checklists prior to intubation of critically ill patients outside a theatre environment can reduce the incidence of adverse events. Four directly relevant papers were found using the reported search strategy and presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. It is concluded that preprocedural checklists may reduce adverse events in these patients, but that the evidence level is low and further matched cohort studies are needed to prove effectiveness.